Implementasi Konstitusi Terhadap Perlindungan Hak Asasi Manusia dalam Prespektif Hukum Tata Negara - Andinia Noffa Safitria; Zahrotul Afifah; Dwi Mei Nandani; Wikha Rahmaleni; Ananda Thalia Wahyu Salsabilla; Kuswan Hadji (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Human rights are important, indivisible and fundamental rights that exist in every human being from the moment of birth. In Indonesia, the 1945 Constitution of the Republic of Indonesia (UUD 1945) serves as the constitutional protection of human rights. The purpose of the Indonesian legal system is to defend and defend human rights. This thesis explores how the Indonesian legal system protects human rights by examining how the constitution is applied in democratic practice in everyday society. The basic human rights law contained in the constitution, the mechanism of protecting human rights in the legal system of the Unitary State of the Republic of Indonesia, difficulties in implementing human rights will be discussed in this examination. The analysis shows that the Indonesian constitution provides a strong legal basis for the defense of human rights. Especially in the right to freedom in democracy within the scope of the state seen from a societal point of view..